Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Physiological and molecular mechanisms of blue light-regulated archeospore formation in Pyropia yezoensis - Li-Fei Yang; Yue-Ting Pan; Hong-Chang Ding; Da-Hai Gao (Aquaculture, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Molecular Mechanisms Underlying Root Adaptation Under Salt Stress - Ding-Ding Zuo; Da-Long Guo; Xiao-Gai Hou (Journal of Plant Growth Regulation, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

A refined framework for assessing seismic direct economic losses of community building portfolios considering vulnerability uncertainty - Jia-Wei Ding; Da-Gang Lu; Zheng-Gang Cao (Engineering Structures, 2026)

Experimental and simulation studies on enhancing passive radiative cooling of stratospheric airship envelopes with microporous polymer film - Yuming Wei; Ming Zhu; Dongxu Liu; Yang Ding; Da Zhao (Advances in Space Research, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Differential light spectrum regulation of oogenesis and spermatogenesis in Plectropomus leopardus - Hui Ding; Lin Li; Da Zheng; Mingjian Liu; Jinyang Xie; Binglin Li; Yuli Li; Zhenmin Bao; Bo Wang; Jingjie Hu (Aquaculture, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Upwelling-driven productivity and temperature-mediated diatom–dinoflagellate succession over the past 3000 years in the East China Sea - Zhangyu Cheng; Shuai Liu; Da-Wei Li; Wupeng Xiao; Yang Ding; Li Li; Meixun Zhao (Quaternary Science Reviews, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

A CNN-LSTM-Attention model for risk prediction of offshore wind turbines - Jia-Xuan Li; Da-Gang Lu; Jia-Wei Ding; Yong Ding; Hao Liu; Libo Chen; Wenbing Wu (Ocean Engineering, 2026)

Design, fabrication and multiple failure behavior of carbon fiber composite circumferential corrugated reinforced cylindrical shells under hydrostatic pressure - Yang-Xu Chong; Jin-Shui Yang; Da-Long Ding; Fang Yang; Hai-Dong Li; Yu-Yin Wei; Er Zhang; Jia-Dong Zeng; Guo-Tao Chen (Ocean Engineering, 2026)

Niche-based filtering governs arbuscular mycorrhizal fungal community variation in temperate grasslands of Northern China - Xinyan Liu; Pengfei Wang; Hanting Qu; Zhiying Ding; Jingpeng Li; Da Xu; Fucheng Ding; Yuying Bao (Applied Soil Ecology, 2026)

Isolation, purification, and functional characterization of porcine fibroblasts across different ages and anatomical sites for cultured meat - Wei Li; Chunyan Da; Moru Deng; Shijie Ding; Shuyu Pan; Xinyue Liang; Chunbao Li; Guanghong Zhou; Changbo Tang (Food Research International, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Key factors affecting atmospheric visibility during the 19th Asian Games in Hangzhou - Yang Wu; Jing Wei; Jiasi Shen; Xiaoyuan Wang; Zheng Xia; Wenlong Zhao; Da Xu; Qian Tang; Jinmei Ding; Xudong Tian; Yuwen Niu; Zhibin Wang; et al. (Atmospheric Research, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

A new polyketide from Penicillium sp. HK-G2 and its inhibitory activity against α-glucosidase - Jie Zhen Shi; Yan-Li Zhang; Jin Hua Yu; Da-Mei Wang; Dong Gan; Zhong-Tao Ding (Natural Product Research, 2025)

Hexafluoropropylene oxide homologues, the novel alternatives to PFOA, induce mitochondrial dysfunction and cytotoxicity in Leydig cells through disrupting SIRT1/PGC-1α signaling pathway - Mei-Ling Le; Jia-Yu Xue; Li-Hai Wu; Xin-Yuan Zhao; Jing Ding; Yang-Yang Yuan; Yi-Qi Wan; Da-Lei Zhang (Toxicology, 2025)

Impact of rotor size and axial spacing on the aerodynamic performance and power generation of offshore floating dual-rotor wind turbines - Ji Zhang; Da Xu; Ding Wu; Xiaohui Huang; Chuang Wen (Ocean Engineering, 2025)

An evaluation approach integrating remedial duration for sustainable mega-site remediation in China - Xin LIU; Peng JIN; Zongshuai YANG; Changlong WEI; Paul BARDOS; Da DING; Zhuanxia ZHANG; Xin SONG (Pedosphere, 2025)

Identification of grape H3K27 methyltransferase genes and their expression profiles during grape fruit ripening - Ding-Ding Zuo; Hao-Ting Sun; Lu Yang; Fang-Hui-Zi Shang; Da-Long Guo (Molecular Biology Reports, 2025)

Risk assessment of spatially distributed assets with generalized seismic fragility models based on machine learning - Jia-Wei Ding; Da-Gang Lu; Zheng-Gang Cao (Soil Dynamics and Earthquake Engineering, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Single Iron Atom with Porphyrin Coordination Environment Decorated Graphited Carbon Nitride for Photocatalytic Selective Semi-Dehydrogenation of THIQ - Jihui Wang; Haoyu Shi; Chengjia Qian; Shuyan Zhang; Kejian Ding; Songmei Wu; Da Wang; Jian Liu; Yu Yu (Chemical Engineering Journal, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Species interactions mediate arbuscular mycorrhizal fungi successional dynamics and glomalin-related soil protein accumulation in volcanic ecosystems - Pengfei Wang; Xinyan Liu; Yaxin Zheng; Hanting Qu; Jingpeng Li; Ruiping Wang; Yu Ji; Da Xu; Fucheng Ding; Peng Zhang; Haijing Liu; Yuying Bao (Applied Soil Ecology, 2025)

Wheat bran supplementation improved polystyrene degradation efficiency of Zophobas atratus larvae by alleviating intestinal injury caused by polystyrene-intake - Cong Liang; Yun Jia; Ren-tao He; Bin Ding; Zheng-da Yang; Xiao-qiang Cao; Jian Zhang (Journal of Hazardous Materials, 2025)

The Role of Hydrogen Peroxide in Fruit Ripening Regulation - Lu Yang; Ding-Ding Zuo; Da-Long Guo (Journal of Plant Growth Regulation, 2025)

Driving sustainability at early-stage innovation in production of zinc oxide nanoparticles - Israel Carreira-Barral; Julieta Díez-Hernández; Elorri Igos; Michael Saidani; Tianran Ding; Tiago Ramos da Silva; Helena Monteiro; Andreas Stingl; Patricia M.A. Farias; Olavo Cardozo; Jesús Ibáñez; Ana García-Moral; et al. (Sustainable Production and Consumption, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Electron delocalization-modulated hydroxyl binding for enhanced hydrogen evolution reaction activity - Da Liu; Peifang Guo; Qiangqiang Wang; Jin Zhou; Mingchang Zhang; Xingyu Ding; Chao Zheng; Hongge Pan; Renbing Wu (Science Bulletin, 2025)

Pioglitazone Modulates Microglia M1/M2 Polarization Through PPAR-γ Pathway and Exerts Neuroprotective Effects in Experimental Subarachnoid Hemorrhage - Yingying Ding; Yue Wang; Ming Qi; Xu Zhang; Da Wu (Molecular Neurobiology, 2025)

Associations of polycyclic aromatic hydrocarbons exposure with serum uric acid and hyperuricemia in US adults: The role of systemic inflammation - Yang Liu; Xuejie Ding; Linling Yu; Da Shi; Ruyi Liang; Wei Liu; Xuezan Huang; Xiuyu Cao; Min Zhou; Weihong Chen (Journal of Environmental Sciences, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Declining trends and regional variations of organophosphate ester contamination in indoor dust from mainland China: Insights from a filed study and meta-analysis - Jing Li; Liu Yang; Yuying Ding; Fei Yang; Hongli Tan; Shuqin Tang; Da Chen (Science of The Total Environment, 2025)

Extraction of antimicrobial peptides from pea protein hydrolysates by sulfonic acid functionalized biochar - Min Liu; Xian-Da Hu; Xiang-Yu Huang; Li Wen; Zhou Xu; Li Ding; Yun-Hui Cheng; Mao-Long Chen (Food Chemistry, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Insights into the accumulation and hepatobiliary transport of bisphenols (BPs) in liver and bile - Jie Ding; Ying Liu; Yanjie Li; Yongheng Huang; Shibo Li; Fei Wang; Da Chen; Bin Lu; Nan Lin (Environmental Research, 2024)

Hydrogen peroxide priming triggers splicing memory in grape berries - Ding-Ding Zuo; Hao-Ting Sun; Lu Yang; Meng-Ling Zheng; Jing Zhang; Da-Long Guo (Plant Molecular Biology, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Lateral transport facilitates terrestrial organic carbon burial in the Santa Barbara Basin over the past 80 years (1937–2018 CE) - Hanyue Xu; Da-Wei Li; Hong-Chun Li; William M. Berelson; Yang Ding; Li Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Source elimination of antibiotic resistance risk in aquaculture water by VUV/sulfite pretreatment - Shuangjing Dong; Huajun Feng; Yao Du; Jingqing Zhou; Jixiao Xu; Da Lin; Danna Ding; Yijing Xia; Meizhen Wang; Yangcheng Ding (Journal of Environmental Management, 2024)

Synergistic ultra-high adsorption and oxidation of arsenic in groundwater by iron-modified biochar: Mechanisms and potential application - Jing Wei; Lina Wang; Yihan Liu; Da Ding; Qun Li; Yousheng Liu; Yun Chen; Meng Mao; Shaopo Deng (Chemical Engineering Journal, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

Research on pollution identification and safety thresholds based on the olfactory effect on a halogenated hydrocarbon contaminated site - Xuwei Li; Wenyi Xie; Ya Zhang; Yun Chen; Mei Li; Lingya Kong; Da Ding; Shaopo Deng (Chemosphere, 2024)

Probing microscale crystallization phenomena: Transforming waste slags into riches - Cong Liang; Zheng-Da Yang; Yu Tan; Bin Ding (Waste Management, 2024)

Electric field induced molecular orientation to construct the composite polymer electrolytes with vertically aligned ion diffusion pathways for stable solid-state lithium metal batteries - Yuanjun Zhao; Mengqiu Gao; Yanyang Qin; Xinyu Da; Xuetian Deng; Xin Jia; Kai Xi; Yaqiong Su; Shujiang Ding; Qiang Rong; Xiangpeng Kong; Guoxin Gao (Chemical Engineering Journal, 2024)

Iron species and sulfur isotopic compositions of authigenic pyrite in deep-sea sediments at southern Hydrate Ridge, Cascadia margin (ODP Leg 204): implications for non-steady-state depositional and diagenetic processes - Chenhui Liu; Shao-Yong Jiang; Xin Su; Xiaopeng Bian; Hai Ding; Da Li; Tao Yang (Frontiers in Marine Science, 2024)
Two accretionary sediment sequences from Sites 1245 and 1252 recovered during Ocean Drilling Program (ODP) Leg 204 at southern Hydrate Ridge were investigated to explore the response of geochemical partitioning of iron and sulfur isotopic composition of authigenic pyrite to non-steady-state depositional and diagenetic scenarios. Five iron species were characterized by a modified sequential extraction procedure that covers almost all iron-bearing minerals in sediment cores, including: (1) iron-bearing carbonates, mainly siderite; (2) ferric (hydr)oxides, probably ferrihydrite and/or lepidocrocite; (3) magnetite; (4) iron-bearing silicates; and (5) pyrite. Highly reactive iron has been accumulated for a long-term steady-state history and its pyritization, to varying degrees, is limited by availability of dissolved sulfide. This causes pyrite and siderite occurred in the same sedimentary layer and shows an inverse relationship between their concentrations. From this, their proportions to highly reactive iron can be chosen for evaluating the degree of sulfidization. A significant change in sulfur isotopic composition of pyrite (-42.4 to +16.8‰ VCDT) indicates that the steady-state conditions are dramatically limited, where the δ 34 S values higher than -20‰ may result from an upward shift of SMT zone close to the seafloor or a sudden, massive depositional event. To explain the downcore sulfidization effects and pyrite δ 34 S values, we developed two categories of conceptual scenarios based on variations in sedimentation rate and methane flux. The geochemical features similar to those derived from each scenario were searched in the sediment columns and the non-steady-state events behind the scenarios were proved to be consistent with the real observations. Thus, iron species and pyrite δ 34 S values can be regarded as a proxy to differentiate different non-steady-state depositional and diagenetic controls on the sedimentary record.

Application of phosphogypsum and phosphate-solubilizing fungi to Pb remediation: From simulation to in vivo incubation - Lingzi Meng; Kejin Ding; Yige Qiu; Yunhui Chen; Hongxun Huo; Dan Yu; Da Tian; Zhen Li (Science of The Total Environment, 2024)

Determining priority control toxic metal for different protection targets based on source-oriented ecological and human health risk assessment around gold smelting area - Yan Zhou; Da Ding; Yuanchao Zhao; Qun Li; Dengdeng Jiang; Zhengyong Lv; Jing Wei; Shengtian Zhang; Shaopo Deng (Journal of Hazardous Materials, 2024)

Can we redevelop ammonia nitrogen contaminated sites without remediation? The key role of subsurface pH in human health risk assessment - Da Ding; Yun Chen; Xuwei Li; Qiang Chen; Lingya Kong; Rongrong Ying; Lei Wang; Jing Wei; Dengdeng Jiang; Shaopo Deng (Journal of Hazardous Materials, 2024)

Natural attenuation of BTEX and chlorobenzenes in a formerly contaminated pesticide site in China: Examining kinetics, mechanisms, and isotopes analysis - Mengjie Wang; Dengdeng Jiang; Lu Yang; Jing Wei; Lingya Kong; Wenyi Xie; Da Ding; Tingting Fan; Shaopo Deng (Science of The Total Environment, 2024)

Estimation of local scour around monopile foundations for offshore structures using machine learning models - Da-Wei Guan; Yu-Xuan Xie; Yee-Meng Chiew; Fan Ding; Tiago Fazeres Ferradosa; Jianhao Hong (Ocean Engineering, 2024)

Comprehensive distribution characteristics and factors affecting the migration of chromium in a typical chromium slag-contaminated site with a long history in China - Yan Zhou; Dengdeng Jiang; Da Ding; Jing Wei; Wenyi Xie; Xin Zhu; Shaopo Deng; Tao Long; Yunjin Wu (Environmental Science and Pollution Research, 2024)

Experimental study on longitudinal shear behavior of prefabricated steel-concrete composite beams with notched connections - Da Huang; Xin Nie; Jiansheng Fan; Ran Ding (Engineering Structures, 2024)

The associations between high-levels of urine benzophenone-type UV filters (BPs) and changes in serum lipid concentrations - Qi Chen; Qianyu Chen; Guanyong Su; Da Chen; Zhen Ding; Hong Sun (Chemosphere, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Medium-sized anammox granules achieve the optimal synergism between AnAOB and HDB via nitrite cycle - Da Kang; Xinyu Wan; Meng Zhang; Shuang Ding; Ping Zheng; Yongzhen Peng (Journal of Cleaner Production, 2023)

Enhancing energy efficiency and thermal satisfaction in office buildings: A comprehensive evaluation of space match strategy - Shiqi Ding; Chengyu Tang; Da Li; Snowil Lopes (Energy and Buildings, 2023)

Effect of PM2.5 air pollution on the global burden of lower respiratory infections, 1990–2019: A systematic analysis from the Global Burden of Disease Study 2019 - Junjie Hu; Runxuan Zhou; Rong Ding; Da-Wei Ye; Yanbing Su (Journal of Hazardous Materials, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Spatiotemporal characteristics and dynamic risk assessment of a multi-solvents abandoned pesticide-contaminated site with a long history, in China - Mengjie Wang; Dengdeng Jiang; Da Ding; Shaopo Deng; Lingya Kong; Jing Wei; Feiyang Xia; Mei Li; Tao Long (Journal of Environmental Management, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

Biotechnological interventions in bamboo plants - Zishan Ahmad; Jaime A. Teixeira da Silva; Anwar Shahzad; Shuyan Lin; Yulong Ding; Muthusamy Ramakrishnan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

The involvement of an HMG-box gene in germ cell genesis in Pyropia haitanensis - Hong-Chang Ding; Long-Chen Tang; Da-Hai Gao; Xing-Hong Yan (Algal Research, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Regulation of reactive oxygen species on production, release, and early germination of archeospores in Pyropia yezoensis - Chao-Feng Teng; Da-Hai Gao; Hong-Chang Ding; Xing-Hong Yan (Algal Research, 2023)

Influences of the 1855 AD Huanghe (Yellow River) Relocation on Sedimentary Organic Carbon Burial in the Southern Yellow Sea - Jianying Liu; Da-Wei Li; Yang Ding; Tiantian Ge; Weifang Chen; Chih-An Huh; Meixun Zhao (Frontiers in Marine Science, 2022)
The Huanghe (Yellow River) supplies large amount of sediments and terrestrial organic carbon (OC) to the eastern Chinese marginal seas. A relocation of the Huanghe outlet from the southern Yellow Sea (YS) to the Bohai Sea occurred in 1855 AD, however, detailed knowledge about the impact of this relocation on sedimentary source and OC burial in Chinese marginal seas is still critically lacking. In this study, we present total OC content and its isotope (δ 13 C), along with bulk total organic carbon (TOC)/total nitrogen (TN) molar ratio and lipid biomarker contents, in a sediment core HH12 from the southern YS with sediment age spanning the last 300 years. We find that TOC and terrestrial lipid biomarker mass accumulation rates were lower between 1855 AD and 1950 AD than that prior to 1855 AD in core HH12; and in accordance, both TOC/TN ratio and δ 13 C records indicate a gradual decrease of terrigenous source contributions to sedimentary OC. This suggests that the relocation of the Huanghe outlet reduced the transport of terrestrial OC to the southern YS. However, the δ 13 C record also indicates a relative increase of terrestrial OC contribution to sedimentary OC after 1950 AD, and the most likely explanation is increased contributions from the old Huanghe delta erosion and Korean rivers. Future studies should focus on better constraining the variations of terrestrial and marine endmembers with δ 13 C and Δ 14 C analyses of specific biomarkers to examine these linkages.

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Influence of Distal Re-entry Tears on False Lumen Thrombosis After Thoracic Endovascular Aortic Repair in Type B Aortic Dissection Patients: A Computational Fluid Dynamics Simulation - Da Li; Tinghui Zheng; Zhan Liu; Yan Li; Ding Yuan; Yubo Fan (Cardiovascular Engineering and Technology, 2021)

Mapping and cloning of quantitative trait loci for phosphorus efficiency in crops: opportunities and challenges - Wei Wang; Guang-Da Ding; Philip John White; Xiao-Hua Wang; Ke-Mo Jin; Fang-Sen Xu; Lei Shi (Plant and Soil, 2019)

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Construction of a small-caliber tissue-engineered blood vessel using icariin-loaded β-cyclodextrin sulfate for in situ anticoagulation and endothelialization - Jingyuan Yang; Keyu Wei; Yeqin Wang; Yanzhao Li; Ning Ding; Da Huo; Tianran Wang; Guanyuan Yang; Mingcan Yang; Tan Ju; Weng Zeng; Chuhong Zhu (Science China Life Sciences, 2018)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

17β-Estradiol protects against apoptosis induced by interleukin-1β in rat nucleus pulposus cells by down-regulating MMP-3 and MMP-13 - Si-Dong Yang; Da-Long Yang; Ya-Peng Sun; Bao-Lin Wang; Lei Ma; Shi-Qing Feng; Wen-Yuan Ding (Apoptosis, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Editorial - Yihui Ding; Guoxiong Wu; Da-Lin Zhang; Renhe Zhang (Journal of Meteorological Research, 2014)

Anterolateral minithoracotomy versus median sternotomy for mitral valve disease: a meta-analysis - Chao Ding; Da-ming Jiang; Kai-yu Tao; Qun-jun Duan; Jie Li; Min-jian Kong; Zhong-hua Shen; Ai-qiang Dong (Journal of Zhejiang University-SCIENCE B, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

The role of chromosomal retention of noncoding RNA in meiosis - Da-Qiao Ding; Tokuko Haraguchi; Yasushi Hiraoka (Chromosome Research, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Cellular automata model as an intuitive approach to simulate complex land-use changes: an evaluation of two multi-state land-use models in the Yellow River Delta - Wen-Juan Ding; Ren-Qing Wang; Da-Qian Wu; Jian Liu (Stochastic Environmental Research and Risk Assessment, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Association between the XRCC3 polymorphisms and breast cancer risk: meta-analysis based on case–control studies - Xiao-Feng He; Wu Wei; Jiao Su; Zi-Xuan Yang; Yi Liu; Ying Zhang; Da-Peng Ding; Wei Wang (Molecular Biology Reports, 2012)

XPD Lys751Gln polymorphism and esophageal cancer susceptibility: a meta-analysis of case–control studies - Da-Peng Ding; Wen-Li Ma; Xiao-Feng He; Ying Zhang (Molecular Biology Reports, 2012)

Saline conducted electric coagulation (SCEC): original experience in experimental hepatectomy - Guo-ping Ding; Li-ping Cao; Da-ren Liu; Ri-sheng Que (Journal of Zhejiang University-SCIENCE B, 2012)

Glypican-3, a novel prognostic marker of hepatocellular cancer, is related with postoperative metastasis and recurrence in hepatocellular cancer patients - Su Ning; Chen Bin; Huang Na; Shen Peng; Ding Yi; Ye Xiang-hua; Zeng Fang-yin; Zheng Da-yong; Luo Rong-cheng (Molecular Biology Reports, 2012)

Ototoxic destruction by co-administration of kanamycin and ethacrynic acid in rats - Hong Liu; Da-lian Ding; Hai-yan Jiang; Xue-wen Wu; Richard Salvi; Hong Sun (Journal of Zhejiang University-SCIENCE B, 2011)

Tannins and nitrogen dynamics in mangrove leaves at different age and decay stages (Jiulong River Estuary, China) - Yi Ming Lin; Jin Wen Liu; Ping Xiang; Peng Lin; Zhen Hua Ding; Leonel da Silveira Lobo Sternberg (Hydrobiologia, 2007)

Metabolic effects of telmisartan in spontaneously hypertensive rats - Yong-Qi Li; Hui Ji; Yi-Hua Zhang; Da-Yong Ding; Xiao-Lei Ye (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Characterization of on-road CO, HC and NO emissions for petrol vehicle fleet in China city - Hui Guo; Qing-yu Zhang; Yao Shi; Da-hui Wang; Shu-ying Ding; Sha-sha Yan (Journal of Zhejiang University-SCIENCE B, 2006)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)